Javanese Culture-Based Numeracy Test Using the Rasch Model - Ninik Zuroidah; Adisa Eka Damayanti; Jerhi Wahyu Fernanda; Burhanudin Syaifulloh (Jurnal Pendidikan Progresif, 2024)
Javanese culture-based numeracy test using the Rasch model. Numeracy is one of the six basic literacies students need to improve in the 21st century. Objectives: This research aimed to develop a numeracy test based on Javanese culture using the Rasch model. Methods: The ADDIE model is used in the numeracy development model. The question grid is based on modified curriculum-13 and the Minimum Competency Assessment (MCA) numeracy framework. Data was obtained from tests aimed at 300 SMP Negeri 5 Kediri City students, which were determined using simple probabilistic random sampling techniques. Quantitative descriptive analysis assisted by SPSS and Jamovi programs was used to analyze reliability, item suitability tests, and difficulty levels. Findings: The research results showed that 50 numeracy questions with Javanese cultural content had been developed, with 17 questions of medium validity and 33 questions of high validity. The reliability estimate is 0.833, which is very high. In the test of item suitability and item difficulty level, it was found that four items, namely items 1, 2, 6, and 9, were not suitable for use in numeracy test, while 46 other items matched the Rasch model and were suitable for use. Conclusion: This research provides important information for further development and analysis studies related to Javanese culture-based numeracy tests. Keywords: test instrument, numeracy, Javanese culture, ADDIE, Rasch model.DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202470